PERANAN TEOLOGI GEREJA BAGI PERTUMBUHAN SPIRITUALITAS KAUM MUDA KATOLIK - Paulus Melo; Antonius Denny Firmanto (Aggiornamento, 2023)
The purpose of this study is to discuss the role of the church in youth ministry which fosters spirituality. Youth ministry is an integrated ministry in the ministry of the church as a whole. Young people are part of the community of the body of Christ who should grow and contribute to the community. The church's service orientation towards young people should also bring young people to the growth of spirituality because spirituality is fundamental in one's spiritual life. For that the church must start thinking about how to produce young people for the future. The church must start by preparing young people who can be relied upon in the future. The church must also provide examples and values ​​of life for young people so they can understand about church life. Youth who are influenced by postmodern culture express their spirituality with unique expressions. This uniqueness is a challenge for the church to find strategic ways so that youth ministry is able to produce services that are oriented towards growing spirituality. In addition, the church must also place young people as part of a community that can fully contribute to the process of growing their spirituality. Therefore, a community-based form of spiritual growth is needed that involves all members of the community so that this spiritual growth can occur in the lives of young people, as well as having an impact on the community because young people are the church.